Analisis Framing Robert N. Entman dalam Konstruksi Citra Purbaya Yudhi Sadewa pada Media Online Kompas.com - Hafiz Mansyur; Abdul Rasyid (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
Online media play a significant role in shaping public understanding through the framing of issues and public figures. This study addresses the limited attention to how media framing constructs legitimacy and public image in Indonesian digital journalism by analyzing the coverage of Kompas.com on Purbaya Yudhi Sadewa using Robert N. Entman’s framing model. The research employs a qualitative approach with framing analysis of ten news articles published in October 2025. Data were collected through documentation and analyzed based on four elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. The findings indicate that Kompas.com constructs Purbaya’s image dynamically through patterns of legitimacy, criticism, conflict neutralization, and positioning as a problem-solving actor. He is portrayed as a professional and rational figure, while also receiving critical framing related to authority and communication style. The framing tends to maintain balance by providing space for clarification and multiple perspectives. These results demonstrate that media framing functions not only as a mechanism of selection and emphasis but also as a process of negotiating public legitimacy in digital journalism. The study contributes to the development of Entman’s framing model by highlighting its contextual application in Indonesian online media.